Ticks and prevalence of tick‑borne pathogens from domestic animals in Ghana - Nimo‑Paintsil, S.C.; Mosore, M.; Addo, S.O.; Lura, T.; Tagoe, J.; Ladzekpo, D.; Addae, C.; Bentil, R.E.; Behene, E.; Dafeamekpor, C.; Asoala, V.; Fox, A.; et al. (Parasites & Vectors, 2022)
Background: Ticks are important vectors of various pathogenic protozoa, bacteria and viruses that cause serious and life-threatening illnesses in humans and animals worldwide. Estimating tick-borne pathogen prevalence in tick populations is necessary to delineate how geographical differences, environmental variability and host factors influence pathogen prevalence and transmission. This study identified ticks and tick-borne pathogens in samples collected from June 2016 to December 2017 at seven sites within the Coastal, Sudan and Guinea savanna ecological zones of Ghana. Methods: A total of 2016 ticks were collected from domestic animals including cattle, goats and dogs. Ticks were morphologically identified and analyzed for pathogens such as Crimean-Congo haemorrhagic fever virus (CCHFV), Alkhurma haemorrhagic fever virus (AHFV), Rickettsia spp. and Coxiella burnetii using polymerase chain reaction assays (PCR) and sequence analysis. Results: Seven species were identifed, with Amblyomma variegatum (60%) most frequently found, followed by Rhipicephalus sanguineus sensu lato (21%), Rhipicephalus spp. (9%), Hyalomma truncatum (6%), Hyalomma rufpes (3%), Rhipicephalus evertsi (1%) and Rhipicephalus (Boophilus) sp. (0.1%). Out of 912 pools of ticks tested, Rickettsia spp. and Coxiella burnetii DNA was found in 45.6% and 16.7% of pools, respectively, whereas no CCHFV or AHFV RNA were detected. Co-infection of bacterial DNA was identified in 9.6% of tick pools, with no statistical difference among the ecozones studied. Conclusions: Based on these data, humans and animals in these ecological zones are likely at the highest risk of exposure to rickettsiosis, since ticks infected with Rickettsia spp. displayed the highest rates of infection and co-infection with C. burnetii, compared to other tick-borne pathogens in Ghana.
Research Article
Keywords: Tick-borne pathogens; Livestock; Ghana; West Africa